Screening for potential strain to produce bioprotein from cheaper carbon source - Jamal, Parveen; Alam, Md. Zahangir; Saleh, Nurul Umi (2006)
Enough production of food and fodder are essential for sustainability. In times to come, the population of developed countries might be stabilized, but it will keep on increasing, in developing countries, at the rate of average four per cent. This will warrant utilization of certain carbon rich sources, which are easily available and can effortlessly be converted into food and fodder, rich in protein and other essential nutrients. The production of bioproteins (proteins derived from micro-organisms) by fermentation of cheaper carbon source is one of the most promising breakthrough of biotechnological innovations, which will certainly increase the availability of high quality affordable proteins in the world and reduce dependence on animals. Due to the increasing demand for bioproteins, the efficient strains, substrate and method must be used for high yield product. In this study, we have made prudent efforts to produce maximum quantity of bioprotein by liquid state bioconversion of wheat flour - a cheaper carbon source having high nutritional value, high carbohydrate percentage and easily available in Malaysia. Screening of five different microorganisms - Aspergillus niger, Phanerochaete chrysosporium, Saccharomyces cerevisiae, Mucor hiemalis and Thricoderma harzianum - was done with fixed process conditions. Bioconversion was done in a 500 ml Erlenmeyer flask having 100 ml of wheat flour with known concentration of 2% (w/v) at a temperature of 270C, agitation of 150 rpm with 2% inoculum (106 spores/ml). Biomass production was recorded every day for six days and the protein content was also determined every day. From the observed results, Mucor hiemalis was found to be as the most potential strain with biomass of about 11.4 g/L on the fourth day of treatment. With this promising result, the amount of bioproteins could be further increased by optimizing process factors. This study may provide a better alternative in agricultural products by converting cheaper carbon source to valuable and quality product bioprotein, which can be used as supplement and additive in the animal feed as well as in chemical and pharmaceutical industries.